Angoisse. Extraits - Anselm Strauss; Barney Glaser (Tracés, 2020)
Anguish: The Case History of a Dying Trajectory (1970) presents discussions between two women, Shirley Teale and Shizuko Fagerhaugh, both nurses and researchers, and the sociologist Anselm Strauss, about the story of a woman, Mrs. Abel, dying in the hospital and accompanied by the two nurse researchers in her last months. Strauss presents the discussions with his collaborator Barney Glaser, within the framework of the grounded theory approach they developed. It is a story that operates on at least three levels: the story of Mrs. Abel as a woman dying of cancer in 1963-1964, whose pain, concerns and anguish are enfolded within a troubling configuration of medical attitudes towards her experience; on a second level it is the story of the two nurses who endeavour to observe and interpret the suffering of someone they are charged with caring for; and finally on a sociological level, a question is posed as to why and how researchers take the pain of others as an object of inquiry.